Thyroid differentiation profile for differentiated thyroid cancer - Anthony J McGoron; Jose M Garcia; Burulça Uluvar; Seza A Gulec (Endocrine Oncology)
Radioactive iodine (RAI) treatment is an established therapeutic tool for ‘differentiated thyroid cancers’. The therapeutic effectiveness is linked to the preservation of the iodine-concentrating ability of the neoplastic tissue, a unique, inherent quality of a normal thyroid gland. Iodine concentration is a function involving the expression of transport proteins and organification. Thyroid differentiation score (TDS) is an integrated quantity, first introduced by The Cancer Genome Atlas (TCGA), conveying the relative expression of proteins involved in histogenesis, morphologic and functional differentiation of thyroid tissue. The concept is well described for the expression of metabolic suppression of thyroid cancers associated with RAI-refractoriness. We evaluated the mRNA expressions of thyroid metabolomics-specific genes, comparing normal thyroid to neoplastic tissue in a cohort where patient-specific paired data were available. Fifty-nine papillary thyroid cancer samples from the TCGA project with matched tumor-normal tissue samples were analyzed. Of the 59 samples, 29 contained a BRAFV600E mutation, seven a RAS mutation, 10 a mutation other than BRAF or RAS, and 14 either no mutation or an unknown mutation. Our analysis demonstrated that there was a significant downregulation of the RAI theranostic transcriptome, much more significant in BRAF-initiated cancers vs RAS-initiated ones. There was also notable heterogeneity in respective mutational categories where individual assessment of the thyroid differentiation profile (TDP) would potentially be clinically relevant for RAI treatment planning. Determination of TDP and development of a theranostic TDS may have an impact on clinical decision making as to the extent of thyroidectomy and postoperative RAI therapy.